The Impact of E-Government on Governance in the Case of ASIA Countries in 2020 - Diana Michel (West Science Interdisciplinary Studies, 2023)
This study aims the impact of each governance indicator in 30 Asian countries through an analysis of the 2020 Worldwide Governance Indicators (WGI) and E-Government Development Index (EGDI). This study uses quantitative methods. Visual analysis of coded data using Google Data Studio with table functionality and SmartPLS version 3.0 software. samples from 30 Asian countries. The results are as follows: First, the effect of his EGDI on WGI, only one of each correlation metric had an invalid value that is voice and accountability with a value of 0.386, suggesting a potential impact on freedom of expression. Association and social media in 30 Asian countries are still low, with an original sample value (O) of 0.824, the sample mean (M) of 0.832, STDEV of 0.043, a t-statistic of 19.318, and P-value of 0.000. Second, according to the data processing results of Google Data Studio, each indicator such as COC, GE, PSA, RL, RQ, VA has a positive value, and among the 30 Asian countries affecting each indicator, Singapore scores very high. Then Pakistan, achieved an average score out of 30 Asian countries. Although this is a negative number, COC, GE, PSA, RL, RQ, and VA indicators still need improvement.